A definition and clinical grading of Modic changes. Issue 2 (27th December 2021) - Udby, Peter M.; Samartzis, Dino; Carreon, Leah Y.; Andersen, Mikkel Østerheden; Karppinen, Jaro; Modic, Michael
Abstract: To provide an up‐to‐date description of knowledge and pitfalls related to the classification, definition and grading of Modic changes (MC) visualized on magnetic resonance imaging (MRI). State‐of‐the‐art review of current knowledge regarding the definition and grading of MC on MRI. MC on MRI have been reported to be associated with low back pain and disability. However, previous studies have shown heterogeneous results in regards to the impact of MC and its clinical relevance in patients with back pain. MC is a term used with considerable variation in the literature. No strict definition has been provided previously, this has contributed to varying diagnostic inclusion criteria, heterogeneous study populations, and discrepancy in results. A definition of MC and a proposal for grading is provided in this state‐of‐the‐art review. MC are important, clinically relevant findings. However, issues with the nomenclature, definition and grading of these changes need to be addressed. Our current review highlights relevant issues related to MC, and provides a definition and grading score for the term MC that includes the Modic type and the extent of vertebral body involvement. Future studies should seek to validate the MC grading score in clinically relevant populations.